Application of newly synthesized titanium (iv) butoxide-cyanopropyltriethoxysilane sorbent for the extraction of aromatic amines in water samples / Mazidatulakmam binti Miskam - Miskam, Mazidatulakmam (2014)
A new titanium (IV) butoxide-cyanopropyltriethoxysilane (Ti-CNPrTEOS) hybrid material was successfully synthesized as sorbent for the extraction of polar aromatic amines. The sorbent was synthesized by hydrolysis and condensation of titanium (IV) butoxide and cyanopropyltriethoxysilane with the presence of hydrochloric acid as catalyst via sol-gel method. Under the optimum synthesis conditions (tetrahydrofuran as solvent, 1.2 M of hydrochloric acid catalyst, 4 mol of water content with ratio of titanium (IV) butoxide and cyanopropylteriethoxysilane of 1:1 and aging temperature of 60°C), the sorbents were characterized by Fourier Transform-Infrared, Field-Emission Scanning Electron Microscopy-Energy, CHN elemental analysis, Brunauer–Emmett–Teller (BET) desorption and thermogravimetric analysis. A solid phase extraction (SPE) method has been developed using Ti-CNPrTEOS sorbent for the determination of aromatic amines and optimum experimental conditions were sample at pH 7, dichloromethane as conditioning solvent, 10 mL sample loading volume, 5 mL of acetonitrile as the eluting solvent. The limit of detection (LOD) and limit of quantification (LOQ) using Ti-CNPrTEOS SPE sorbent (0.01-0.20; 0.03-0.61 µgL-1) were absolutely lower compared with those achieved using silica-cyanopropyl (Si-CN) SPE sorbent (0.23-1.47; 0.75-4.91 µgL-1) and C18 SPE sorbent (0.36-0.98; 1.54-2.56 µgL-1). The recoveries and repeatability obtained from water samples using the sol–gel Ti-CNPrTEOS SPE sorbent were 57–99% and RSDs 1–4%, n=5. The lowest recovery of non-polar diethylaniline, DEA (57%) indicated that the sorbent was very selective towards the extraction of polar aromatic amines. Ti-CNPrTEOS sorbent was also successfully applied as sorbent for solid phase membrane tip extraction (SPMTE). Under the optimum extraction conditions; 15 mL of sample at pH 7, acetonitrile as conditioning and desorption organic solvent, extraction time of 15 min and desorption time of 15 min, the method showed good linearity with acceptable reproducibility (RSD 2.5 – 3.6%, n = 5) and LOD and LOQ for Ti-CNPrTEOS SPMTE (0.13 – 6.23 ngL-1; 0.53 – 5.67 ngL-1) were lower with those achieved by C18-SPE (0.36-0.98 gL-1; 1.54-2.56 gL-1). The application of the Ti-CNPrTEOS SPMTE sorbent was successfully carried out by analysis of aromatic amines in river water sample with the recovery between 49–99%. The lowest recovery of non-polar DEA (49%) indicated that the sorbent was very selective towards the extraction of polar aromatic amines. The newly developed method using Ti-CNPrTEOS sorbent was proven as a simple, rapid, cheap and solvent efficient extraction technique.